2018
DOI: 10.1002/eji.201847639
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the balance between Th2 and Th2/1 hybrid cells affects parasite nematode fitness in mice

Abstract: T-helper type 2 (Th2) responses are central to the control of helminth infections, but sensitive to opposing cytokine signals favoring Th1 priming. We previously reported on GATA-3 + T-bet + Th2/1 hybrid cell differentiation in helminth mono-infections, resulting in a substantial proportion of cells coproducing IFN-γ next to Th2 cytokines. Here, we demonstrate Th2/1 cells as the major source of parasite-specific IFN-γ production in acute and chronic infections with the enteric nematode Heligmosomoides polygyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Parasites have developed refined machinery to evade the host's immune system by manipulating its response (Gomes et al, 2016). It is well known that T-helper type 2 (Th2) responses are central to parasitic infections, and can participate in regulation of host's immune system (Affinass et al, 2018). Th2 responses can create an anti-inflammatory immune microenvironment and improve host metabolic disorders (van der Zande et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasites have developed refined machinery to evade the host's immune system by manipulating its response (Gomes et al, 2016). It is well known that T-helper type 2 (Th2) responses are central to parasitic infections, and can participate in regulation of host's immune system (Affinass et al, 2018). Th2 responses can create an anti-inflammatory immune microenvironment and improve host metabolic disorders (van der Zande et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, obesity is a main public health concern since obese individuals are at a greater risk of developing chronic disease and often present clinical parameters of metabolic syndrome (MetS), insulin resistance, and systemic markers of chronic lowgrade inflammation (Alberti et al, 2005;Andersen et al, 2016;Affinass et al, 2018). Adipose tissue accumulation is a common clinical phenomenon in obese individuals (Gijs, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine-driven phenomenon defined as plasticity has also been shown for ILC. As such, it has been observed that NKp46 + ILC3 can differentiate to ILC1 and vice versa (reviewed in Klose et al, 2020), and likewise ILC2 have shown plasticity to ILC1 and ILC3 (Bal et al, 2016, Ohne et al 2016, Lim et al, 2016, Huang et al, 2015and Zhang et al, 2018, Golebski et al, 2019. In humans and mice, IL-12 and IL-18 appear to be the most potent factors to induce T-bet and IFN-γ in ILC2 (Bal et al, 2016, Ohne et al 2016, Lim et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that plasticity in T cells is not always absolute. CD4 + T cells coexpressing T-bet and RORγt or T-bet and GATA3 expression have been characterized (Jenner et al 2009, Affinass et al, 2018, Peine et al, 2013. NKp46 + ILC3 are known to express RORγt and T-bet, but it is not known whether ILC exist that co-express GATA3…”
Section: Introductionmentioning
confidence: 99%